Microstructural Features, Tensile Properties, and Impact Toughness of Linear Friction Welded High-Temperature Alloy Joints for Blisk Assembly Applications - C. Mukundhan; P. Sivaraj; V. Balasubramanian; Tushar Sonar; Vijay Petley; Shweta Verma (Advances in Materials Science and Engineering)
The main objective of this investigation is to analyze the microstructure, tensile properties, and impact toughness of Ti6Al4V alloy joints developed using optimized parameters of linear friction welding (LFW) for gas turbine blisk assembly applications. The 6 mm thick plates of Ti6Al4V alloy were joined using a friction time of 40 sec, a friction pressure of 20 MPa, a forging pressure of 10 MPa, a forging time of 3 sec, and an oscillating frequency of 14 Hz. The different regions of joints were analyzed using a stereo zoom microscope. Optical and scanning electron microscope (SEM) was used for analysing the microstructural features of joints. The room temperature tensile properties, hardness, and impact toughness of LFW-Ti6Al4V alloy joints were evaluated and correlated to the microstructural features of weld region. The fractured sections of tensile and impact toughness specimens of joints were analyzed using SEM and the failure of joints was correlated with the hardness survey. Results showed that the LFW-Ti6Al4V alloy joints developed using the optimized parameters exhibited a tensile strength (TS) of 1015 MPa, a yield strength (YS) of 940 MPa, and an elongation (EL) of 8%. The joints revealed 98.54%, 95.91%, and 66.67% of tensile strength, yield strength, and ductility of the parent metal. The LFW joints disclosed impact toughness (IT) of 17.2 J which is 89.77% impact toughness of the parent metal. The superior tensile properties and impact toughness of LFW-Ti6Al4V alloy joints are mainly attributed to a greater degree of refinement of α + β grains in the weld interface, which offers greater resistance to tensile deformation and crack propagation.